HUBUNGAN TINGKAT PENGETAHUAN HYGIENE SANITASI MAKANAN DENGAN PERILAKU PENGELOLA KANTIN SEKOLAH DASAR - Hersah Purbasari; I Wayan Sudiadnyana; Nengah Notes (Jurnal Kesehatan Lingkungan (JKL), 2022)
Food handler is a person who directly manages food and can be an intermediary for the entry of a disease into food. From the training done in the elementary school canteen in South Kuta Subdistrict, traders still found lacking in hygiene, such as not using aprons, hair coverings, and work clothes. The purpose of this study was to determine the relationship of the level of knowledge of food sanitation hygiene with the behavior of elementary school canteen managers in the District of South Kuta, Badung with a cross sectional approach and data analysis with Spearman correlation statistical analysis techniques. There is a relationship between the level of knowledge of food hygiene sanitation canteen manager with behavior (r of  0.574 and p = 0.000). Then it can be concluded that there is a relationship between the level of knowledge and the behavior of elementary school canteen managers in South Kuta Subdistrict with moderate relationship strength. It is recommended for South Kuta Healt Center elementary schools to carry out routine supervision at least once a month for hygiene food management and canteen  sanitation. Further research is needed that influences behaviors such as attitudes, sanitation facilities, equipment, locations and buildings.